Store-operated calcium entry and the localization of STIM1 and Orai1 proteins in isolated mouse sinoatrial node cells - Liu, Jie; Xin, Li; Benson, Victoria L.; Allen, David G.; Ju, Yue-Kun (Frontiers in Physiology, 2015)
In many non-excitable and excitable cells, store-operated calcium entry (SOCE) represents an additional pathway for calcium entry upon Ca2+ store depletion. In a previous study, we demonstrated SOCE activity in intact mouse cardiac pacemaker tissue, specifically from sinoatrial node (SAN) tissue. However, store content as a key determinant of SOCE activity is difficult to measure in intact SAN tissue. Therefore, to investigate the interaction between SOCE and store content and its role in cardiac pacemaking, it is necessary to investigate SOCE activity in single cardiac pacemaker cells. Furthermore, recent studies in other tissues have identified two new proteins involved in SOCE, stromal interacting molecule (STIM), which is an ER Ca2+ sensor, and the surface membrane channel Orai, a prototypic gene encoding for SOCE. However, whether STIM and Orai are expressed in native pacemaker cells is still unknown. In this current study, we examined SOCE activity in single firing pacemaker cells isolated from mouse sinoatrial node tissue. We found a significant rise in Ca2+ entry in response to Ca2+ store depletion. SOCE blockers reduced the amplitude and frequency of spontaneous Ca2+ transients and reduced Ca2+ store content. We demonstrated for the first time that STIM and Orai are expressed in pacemaker cells. After store depletion, STIM1 redistributed to the cell periphery and showed increased co-localization with surface membrane located Orai1, indicating a possible involvement of these proteins in SOCE activity in native cardiac pacemaker cells. These results suggest the novel concept that SOCE plays a functional role in regulating intracellular Ca2+ of cardiac pacemaker cells.